Satisfaction with health care services in young people with cerebral palsy in the transition period: results from a European multicenter study - Muehlan, Holger; Alvarelhao, Joaquim; Arnaud, Catherine; Cytera, Chirine; Fauconnier, Jerome; Himmelmann, Kate; Marcelli, Marco; Markwart, Henriette; Rapp, Marion; Schmidt, Silke; Thyen, Ute (Frontiers in Medicine, 2024)
Background: Young people with chronic health conditions and disabilities rely on the health care system to maintain their best possible health. The appropriate delivery and utilization of health care services are key to improve their autonomy, self-efficacy and employment outcomes. The research question of our study is directed towards investigating if poor availability and accessibility of health care services in general, as identified by unmet needs in health care, are associated with dissatisfaction with health care.Methods: Within a European multicenter observational study, 357 young adults with cerebral palsy aged 19 to 28 were included. We assessed special health care needs, utilization of health care services, and satisfaction with health care applying the short-form of the YHC-SUN-SF, environmental and social variables (EAEQ) as well as indicators for severity of condition and functionality. We used correlation analyses to explore associations between satisfaction with health care and respective indicators related to availability and accessibility of health care services as well as severity of the condition. In addition, we included reference values for satisfaction with heath care from young adults with various chronic conditions assessed within population-based surveys from some of the European countries included in the study. We identified several unmet health care needs, especially for widely used and established services. Satisfaction with health care was moderate to high and almost consistently better for the sample of young adults with cerebral palsy as compared to reference values for young adults with various chronic conditions assessed within general population surveys. Correlation coefficients between satisfaction with health care and utilization of services and (unmet) health care needs were low, also with different indicators for severity of the condition or functionality.Young adults with cerebral palsy reports of unmet health care needs varied largely but showed substantial deficits in some aspects. This seems to have no impact on the satisfaction with health care those patients currently receive. We conclude that these are two different constructs and somewhat independent indicators to evaluate the quality of health care. Clinicians and other practitioners should consider this distinction when monitoring patient needs in their daily practice.